2015
DOI: 10.1016/j.hlc.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Cardiac Rehabilitation Maintenance Programs: Use and Effects

Abstract: Participation in community-based CR maintenance programs is associated with health benefits but these programs are not accessed by a diversity of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Currently, a very small percentage of eligible CAD patients participate in maintenance CR programs [4]. In addition, there is a paucity of information regarding maintenance CR programs despite findings that such programs are associated with health benefits and facilitate management of cardiovascular risk factors [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a very small percentage of eligible CAD patients participate in maintenance CR programs [4]. In addition, there is a paucity of information regarding maintenance CR programs despite findings that such programs are associated with health benefits and facilitate management of cardiovascular risk factors [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with cardiovascular disease participating in community-based maintenance CR programs, session attendance was positively correlated with peak oxygen consumption and first-year attendance was strongly correlated with attendance in subsequent years [24]. Therefore, understanding the reasons for attendance and non-attendance of maintenance CR programs is essential for promoting longterm exercise adherence in graduates of outpatient CR programs and facilitating their transition to maintenance CR programs.…”
Section: Discussionmentioning
confidence: 99%
“…They are also shown to be efficacious [104][105][106][107] . The offering of alternative models was first reported in a 1997 publication from England and Wales 25 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, Liebs et al showed that aquatic therapy in patients following knee replacement had the effect size of nonsteroidal anti‐inflammatory medications in management of continuing osteoarthritis. Similarly, Mandic et al showed that a community‐based cardiac rehabilitation program improved survival and decreased both hospitalizations and required procedures in patients with cardiovascular disease. Maintenance programs for diabetics have focused on the most common complications such as ophthalmic and foot issues, which were influenced by the patient's age, health literacy, behavioral assessment, and economic situation .…”
mentioning
confidence: 96%
“…In medicine, recall and maintenance protocols have been increasingly emphasized to manage and improve patient health outcomes . Human lifespans are increasing, and management of chronic diseases and associated morbidities has increased the emphasis on patient‐centered management of professionally directed recall and maintenance programs . For example, Liebs et al showed that aquatic therapy in patients following knee replacement had the effect size of nonsteroidal anti‐inflammatory medications in management of continuing osteoarthritis.…”
mentioning
confidence: 99%